Kajian Faktor Internal dan Eksternal UMKM Wanita di Sektor Fashion pada Kecamatan Ngunut, Kabupaten Tulungagung, Jawa Timur - Della Yesica Rani; Lucky Nugroho; Zulfahmi Zulfahmi (Institut Nalanda, 2023)
The purpose of this study was to analyze the external and internal factors of women's SMEs in the fashion sector. The method used in this study is qualitative to understand and explain phenomena or events through an analysis of the external and internal factors of women's SMEs in the fashion sector. The samples in this study were 15 women's SMEs in the fashion sector in Ngunut Village, Tulungagung Regency, East Java. Therefore, this research is limited by the formulation of the problem: (i) What external factors are considered by SMEs women in the fashion sector in doing business?; (ii) What internal factors are considered by SMEs in the fashion sector in doing business? The results of this study are (i) External factors that are of concern to women SMEs in the fashion sector are product quality and family support, while other factors such as business location, capital and permits have not become their focus; (ii) The internal factor that is the focus of women's MSMEs is marketing, especially marketing their products through online channels, while the financial management factor for them has not received special attention. Therefore, the implication of this research is to provide information and references for stakeholders who are concerned about the development of women's MSMEs in the fashion sector in Ngunut Village. The update of this research related to the object of research is that the research is women's SMEs in the field of fashion and in Ngunut Village, which is currently still limited.